PERKEMBANGAN HUBUNGAN MILITER DENGAN SIPIL DI INDONESIA - Setiawan, David; Octavianus, Christopher; Janis, Demas; Winadi, Guguh; Abdullah, Yanuar; Umasugi, Taufik; Suyuti, Handika (Global and Policy Journal of International Relations, 2013)
ABSTRACTThe military has an active and making role’s the politics in Indonesian government at New Order Era. Writers such as Huntington's theory marking read about the military-Civil Affairs on citizens with Agency Theory. In Indonesia, wave of reform also participated in the larger open space for discussion civil-military relations are associated with the democratic process. During this civil-military relations is not only built on military doctrine, which doctrine is less popular among the civil society and its main doctrine was never a debate among the public discourse. So that explains that military professionals can happen if they do not interfere in politics so future formation of a democratic government that includes the rule of law, public accountability in terms of the delicate balance of military autonomy in personnel policy, determining the level of power, issues of education and military doctrine and ultimately think and formulate and determine policy in the field of defense that civil-military relations that harmony must be built within the framework of democracy and mutual trust and mutual cooperation.Keywords: Civil-Military relations, Civil Democracy ControlDOI:https://doi.org/10.33005/jgp.v1i01.2012